Temporary 'castration' for cattle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Farmers can now temporarily castrate their young bulls, thereby making handling much easier. They can also temporarily spay their young heifers or cull cows to prevent unwanted pregnancies. Temporary castration or spaying can be brought about by...